Gamification as a Pedagogical Model to Increase Motivation and Decrease Disruptive Behaviour in Physical Education - Marta Soriano-Pascual; Alberto Ferriz-Valero; Salvador García-Martínez; Salvador Baena-Morales (MDPI AG, 2022)
The application of gamified learning in physical education is becoming increasingly popular. The aim of this work was to compare the effects of gamification versus traditional methodology to check whether there were differences in the attitudes of the students. A quasi-experimental design study was carried out. The sample consisted of 66 students in Secondary Education. Three questionnaires, POSQ (Perception of Success), BPN (Basic Psychological Needs) and CCDEF (Disruptive Behaviour in Physical Education), were used in both groups before and after carrying out each proposal. Firstly, an independent samples Student's t-test was performed. The results showed significant final differences in all variables except two: competence (p = 0.068) and aggressiveness (p = 0.136). Secondly, a paired samples t-test was performed. In this case, the control group showed a significant decrease in the variables task orientation (p = 0.004) and autonomy (p < 0.001). According to the experimental group, all variables showed significant differences (p < 0.05), except for two, competence (p = 0.223) and aggressiveness (p = 0.056). Therefore, it was concluded that, with the gamified learning, the students expressed higher levels of task orientation, all BPNs and lower levels of disruptive behaviours than the students who were subjected to the traditional methodology. This kind of intervention can help to improve the quality of education as set out in the SDGs through Quality Education.